Changes in transcription and phospho-signalling in breast tumour hypoxia and hypoxia-reoxygenation - Aboalmaaly, Amna (2024)
Hypoxia (Low oxygen) is found in 50% of breast cancers. Clinically, hypoxia is associated with increased invasion, metastasis, therapy resistance, and worse patient survival. Hypoxia drives major hallmarks of cancer phenotypes, including invasion. Breast cancer adaptation to hypoxia is regulated by the HIF transcription factors and epigenetic modifications. In addition, hypoxia modulates signalling pathways. Hypoxic tumour cells can become reoxygenated as they invade away from hypoxic tumour regions or via hypoxia-induced tumour vascularisation. We investigated the impact of hypoxia-reoxygenation on gene expression, signalling, and cell phenotypes. Our study involved examining the changes in gene expression in hypoxia and hypoxia-reoxygenation in MDA-MB-231 and MCF7 cell lines using RNA sequencing. The analysis revealed significant changes in gene expression in hypoxia (1537 and 1965 genes, respectively) and in hypoxia-reoxygenation (2091 and 737 genes, respectively). A considerable number of gene expression changes induced by hypoxia were sustained upon reoxygenation, with 38% in MDA-MB-231 and 11.5% in MCF7. These genes were found to be enriched for metabolic processes and signalling pathways such as Wnt and TGFβ signalling. We also examined the expression of these genes in breast tissues using transcriptomic and clinicopathological data. We discovered that several genes such as CST1, MUC1, CDH2, and EGLN3, which are known to be associated with metastasis and poor prognosis in breast cancer patients, were significantly expressed in TNBC and HER2(-ve) tissues. Furthermore, we explored the possible mechanism by which the changes in gene expression induced by hypoxia are sustained upon hypoxia-reoxygenation. We found that activation of growth factors under hypoxia might initiate a positive feedback loop responsible for this phenomenon.